2014
DOI: 10.2989/1814232x.2014.923783
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the occurrence of a second killer whale morphotype in South African waters

Abstract: Killer whales

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Together this evidence supports the theory that this flat‐toothed morphotype frequently predates on sharks (Best et al. ).…”
Section: Dietary Specialization and The Concept Of Ecotypessupporting
confidence: 88%
See 2 more Smart Citations
“…Together this evidence supports the theory that this flat‐toothed morphotype frequently predates on sharks (Best et al. ).…”
Section: Dietary Specialization and The Concept Of Ecotypessupporting
confidence: 88%
“…Although little is known about the behavior and ecology of killer whales in South African waters, studies have shown the existence of at least two morphotypes, which differ in size and a number of other morphological traits (Best et al. ). Due to limited knowledge on the diet and ecology of these species, they cannot be classified as separate ecotypes (de Bruyn et al.…”
Section: Dietary Specialization and The Concept Of Ecotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several killer whale populations specialise on a narrow range of prey and can be morphologically and genetically distinct. A rare offshore morphotype of killer whale was described off South Africa by Best et al, (2014). The following year, a distinctive pair of adult males of this morphotype, appeared in the region, and preyed upon various shark species, including white sharks Carcharodon carcharias, extracting and consuming their lipid rich livers (Engelbrecht et al, 2019;Towner et al, 2022a).…”
Section: Lungementioning
confidence: 99%